Some common strategies to deal with non-equivalence in the translation of Vietnamese traditional costumes - Phạm, Thị Hà Chuyên (2020)
The research examines and offers strategies to deal with non-equivalence in the translation of Vietnamese traditional costumes. The study is conducted to find out effective strategies to help translators in general and those who translate Vietnamese traditional costumes in particular. To obtain the intended goal, the samples are mostly collected from the translation of the book “Trang phục cổ truyền các dân tộc Việt Nam” by Ngô Đức Thịnh and the translation of the book “Trang phục Việt Nam qua các thời đại” by Đoàn Thị Tình. Through the collection and analysis of the samples, the research introduced the strategies available for dealing with the stated problem. Each strategy is presented with typical examples to facilitate reader’s comprehension. Additionally, the author of this graduation paper also makes a list of samples and their translations as a source of reference for those who are interested.